Implementasi Taksonomi Barrett untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Kelas VII - Umamy, Etty; Bactiar, Hamid; Nadhiroh, Khoirun; Mawadah, Ilma Maretiana; Farida, Umi (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2025)
Reading comprehension is an essential skill in education, yet it remains a challenge for many students in Indonesia. The low level of reading comprehension ability is often caused by the lack of instructional strategies that emphasize higher-order thinking skills. This study aims to analyze the effectiveness of implementing Barrett’s Taxonomy in improving the reading comprehension skills of seventh-grade students at SMP Negeri 11 Malang. The research employed Classroom Action Research (CAR) using the Kemmis & McTaggart model, consisting of two cycles. The participants were seventh-grade students, with data collected through pre-tests, post-tests, observations, and interviews. Data analysis was conducted using quantitative (t-test and effect size) and qualitative (thematic analysis) approaches. The findings indicate a significant improvement in students' reading comprehension after implementing Barrett’s Taxonomy, particularly in inferential, evaluative, and appreciative comprehension. The t-test results showed a significant increase in post-test scores compared to pre-test scores (t = 6.89, p < 0.05), with an effect size of 1.24, indicating a substantial impact on reading comprehension. Furthermore, observations and interviews revealed that this strategy enhanced students’ engagement in reading activities. In conclusion, Barrett’s Taxonomy is effective in improving reading comprehension skills and can serve as an alternative strategy for teachers to develop higher-order thinking skills in reading instruction.